Tri Hita Karana and Organizational Culture in Society 5.0: Effect on Adaptability, Consistency, Involvement, and Mission - Subhaktiyasa, Putu Gede; Sintari, Silvia Ni Nyoman; Andriana, Kiki Rizki Fista; Sumaryani, N. Putri; Werang, Basilius Redan; Sudiarta, I Nyoman (Jurnal Ilmiah Manajemen & Bisnis, 2024)
Tri Hita Karana is the local wisdom of the Balinese people that emphasizes the harmonization of relationships with God, fellow humans, and nature and is predicted to create an organizational culture in Society 5.0. However, studies showing the influence are still limited. Therefore, this study examines Tri Hita Karana's influence on adaptability, consistency, engagement, and mission as an organizational culture. This study is a quantitative study with an ex post facto approach involving 164 nurses with a purposive sampling technique. Data were collected using a closed questionnaire with a five-point Likert scale. The evaluation used PLS-SEM with a second-order formative reflective model approach for theoretical studies. The evaluation used SEM-PLS with a second-order formative reflective model approach. The main findings of this study identified that Tri Hita Karana affects organizational culture. Tri Hita Karana, which consists of spiritual, social, and ecological values, has a direct positive effect on adaptability, consistency, involvement, and mission. The study also indicated that the influence on adaptability has a higher effect size than other dimensions. The findings provide an understanding of organizational management and encourage them to consider the concept of Tri Hita Karana as an organizational culture for organizational sustainability in the era of Society 5.0.